A web-based interrogative ontology retrieval application for unstructured documents - Sidi, Fatimah; A. Jabar, Marzanah; Ishak, Iskandar; Mustapha, Aida (Advanced Institute of Convergence Information Technology, 2015)
This paper presents an implementation of Retrieval Interrogative Ontology Analysis application based on the MalayIK-Ontology approach. This application enables querying in simple ways, while increasing human understanding of unstructured document in Malay language. To evaluate the application, a survey is conducted to measure the level of satisfaction of the application by 30 participants. Results from the questionnaires analysis show that the interrogative contextual information is able to facilitate human understanding of unstructured documents as it is supported by additional information annotation. The analysis also concludes that the Malay knowledge representation by concepts is able to generalize the Malay common language as knowledge representation.